Addressing maternal mental health: A crucial imperative for Nepal's wellbeing (Journal of Psychiatrists' Association of Nepal, 2024)
Maternal mental health is a cornerstone of holistic healthcare, yet its significance often remains overshadowed in the global discourse on maternal and child health. In Nepal, a country with improved statistics on maternal mortality over the years, the issue of maternalmental health still remains a matter of public health concern, with countless mothers and their families suffering in silence. This editorial aims to shed light on the urgency of the need to prioritize maternal mental health within the broad healthcare agenda in Nepal and the need to integrate mental health within routine maternal health care programs.